Acceptance and use of technology evaluation on insurance data processing system (Care Tech): a case study on insurance company in Indonesia - Durachman, Yusuf; Suhaimi, Mohd Adam; Selpiana, Selpiana; Nida’ul Hasanati, Nida’ul Hasanati (IEEE, 2017)
Insurance data processing system used by PT. Asuransi Takaful Umum is a system Care Tech. Care Tech System is a system designed for general data processing such as vehicle insurance, fire, property, and others with a web-based base that can be accessed online. During implemented since October 2013, Care Tech system has not been evaluated in terms of user acceptance. The purpose of this study was to determine the factors that influence user acceptance Care Tech system and also provide recommendations to the company PT. Asuransi Takaful Umum which can be used as a decision-making for the development of the next system. This study uses a model to evaluate the Unified Theory of Acceptance and Use of Technology (UTAUT). Variables used in this research that performance expectancy, effort expectancy, social influence, facilitating conditions and behavioral intention. Tests conducted variables include validity, reliability, normality test, multicollinearity, heteroscedasticity test and multiple linear regression tests using the tools of IBM SPSS version 22 and Ms. Excel 2007. The results of this study showed that the variables of performance expectancy, effort expectancy, social influence significant effect on the dependent variable is behavioral intention. While variable conditions facilitating no significant effect on the dependent variable behavioral intention.